Tanzania’s compliance with international law on children in conflict with the law: A case study of Zanzibar - Amour, Chum K (Mzumbe University, 2024)
A dissertation submitted to Mzumbe University as a partial fulfilment of the requirements for the Award of Master’s Degree of Laws in International Law (LL.M. IL) of Mzumbe University